An Investigation of Student Teachers' Anxiety Related to the Teaching Practicum - Charisma, Dila; Nurmalasari, Puteri (Universitas Muhammadiyah Jember, 2020)
This study aims at investigating the student teachers’ anxiety related to the teaching practicum as well as the factors that contribute anxiety during teaching practicum, and exploring the student teachers’ strategies in overcoming their anxiety during teaching practicum. Qualitative research with a case study approach employed in this study. STKIP Invada Cirebon was chosen as the site and English student teachers were the participants of this study who did teaching practicum at SMK RISE Kota Cirebon, while the data were collected through interview and weekly journal. This study discover that students teachers’ anxiety related to the teaching is situation-specific anxiety, and the factors contribute anxiety can be grouped into six categories: being not familiar with the situations in the classroom, being observed by mentor or supervisor, incompetence in teaching, not match with expectations, less English proficiency, and classroom management. So that this study also identifies six categories of coping strategies employed by student teachers: adaptation, preparation, build a good relationship with the mentor and the students, self confidence, positive thinking, and keep calm and enjoy it. The findings of this study give insight for supervisor university, mentor, and student teachers about anxiety may arise during teaching practicum. Key words: Anxiety; Student Teachers’ Anxiety; Teaching Practicum; Cause of Anxiety; Strategies in Overcoming Anxiety.